Urinary acute kidney injury biomarkers in very low-birth-weight infants on indomethacin for patent ductus arteriosus - Waldherr, Sina; Fichtner, Alexander; Beedgen, Bernd; Bruckner, Thomas; Schaefer, Franz; Tönshoff, Burkhard; Pöschl, Johannes; Westhoff, Jens (Pediatric research, 2019)
Serum creatinine (SCr)- or urine output-based definitions of acute kidney injury (AKI) have important limitations in neonates. This study evaluates the diagnostic value of urinary biomarkers in very low-birth-weight (VLBW) infants receiving indomethacin for closure of a patent ductus arteriosus (PDA). Prospective cohort study in 14 indomethacin-treated VLBW infants and 18 VLBW infants without indomethacin as controls. Urinary biomarkers were measured before, during, and after indomethacin administration. Indomethacin therapy was associated with significantly higher SCr concentrations at 36, 84, and 120 h compared to controls. At 36 h, three indomethacin-treated patients met the criteria for neonatal modified Kidney Disease: Improving Global Outcomes (KDIGO) AKI. The product of urinary tissue inhibitor of metalloproteinase-2 and insulin-like growth factor-binding protein 7 ([TIMP-2]•[IGFBP7]) was significantly elevated in the AKI subgroup at 12 h (P < 0.05), hence 24 h earlier than the increase in SCr. Urinary neutrophil gelatinase-associated lipocalin (NGAL) and calprotectin were significantly increased in the indomethacin group at 12 h (P < 0.05), irrespective of fulfillment of the AKI criteria. Urinary kidney injury molecule-1 (KIM-1) was not significantly altered. While urinary [TIMP-2]•[IGFBP7] proves valuable for the early diagnosis of neonatal modified KDIGO-defined AKI, elevated urinary NGAL and calprotectin concentrations in indomethacin-treated VLBW infants not fulfilling the AKI criteria may indicate subclinical kidney injury.